Improved Identity Based Encryption System (IIBES): A Mechanism for Eliminating the Key-Escrow Problem - Maitri Patel; Rajan Patel (Emerging Science Journal, 2021)
A revolutionary change to public-key cryptography can be considered as an Identity Based Cryptography (IBC) in which identity of the receiver is being used as a public key for encrypting a message and Key Generation Centre (KGC). IBC will generate and distribute the private key to each user to decrypt a message. The thought behind presenting the scheme was to improve and reduce the complexity of certificate and key management, but it also gives rise to key escrow problem, access to encrypted information to unauthorized users. The paper represents Improved Identity-Based Encryption Scheme (IIBES) for Domain Name System (DNS) security which provides confidentiality and authentication through modified identity based encryption and identity based digital signatures. The IIBES comprises key revocation mechanism for non-revoked users and also eliminates key escrow problem. Thus, the IIBES aids to implement the identity-based cryptography more safely in reality and protects DNS against cache poisoning, spoofing attack and masquerade attack. Doi: 10.28991/esj-2021-01259 Full Text: PDF